The necessity of early anti-inflammatory therapy initiation in cases with mild-to-moderate COVID-19: A personal experience from an attending pharmacist and his resident - Ghasemiyeh, Parisa; Mohammadi-Samani, Soliman (Acta Biomedica Atenei Parmensis, 2021)
I am a professor and attending pharmacist in the field of pharmaceutical sciences and writer or co-author of at least 5 manuscripts about different aspects of COVID-19. More than 15 months from the first report of COVID-19, over 120 million people all over the world infected by this virus, and more than 2.5 million of them have died. Although different treatment approaches have been proposed, management of the COVID-19 patients is steal remained controversial. In this regard, I want to share my personal experience from the exposure to the coronavirus and the consequence of this infection on my health status. I am a 51 years old male, known case of hypertension, dyslipidemia, and chronic kidney disease. During working hours of colleagues in the Faculty of Pharmacy, I visited one of my colleagues in his office. After leaving the Faculty, my colleague declares that his RT-PCR test of COVID-19 is positive and it took 3 days for me to experience the first sign of the COVID-19 as fever. Many complications have occurred for me during the different stages of COVID-19 infection that I shared and explained in detail with the suggested pharmacotherapies. According to the pathophysiology of COVID-19 infection and my personal experience during COVID-19 infection, I want to emphasize the necessity of early initiation of anti-inflammatory agents including corticosteroids and colchicine in high-risk patients with mild-to-moderate COVID-19 pneumonia who shows respiratory system involvement, in order to prevent progression to the severe and critical stages of this disease.